Obtenção de açúcares fermentescíveis, plataformas químicas, bio-óleo e carvão a partir do processamento hidrotérmico da serragem - Puhl, Bruna Arnold (2024)
In this research, pine wood sawdust was subjected to hydrothermal processing of subcritical hydrolysis and subcritical liquefaction, synergistically, in semi-continuous operation mode, in order to evaluate the production of fermentable sugars (arabionosis, cellubiose, xylose and glucose) platforms. chemicals (acetic, formic and levulinic acids, as well as furfural and hydroxymethylfurfural) bio-oil and hydrochar. The influence of temperature (260, 300 and 340 °C) and the solvent/feed ratio (25 and 50 g H2O /g biomass) were the parameters considered to evaluate the product yield, kinetic profiles and their properties. The pressure used was 20 MPa and the reaction time was 30 min. For fermentable sugars and chemical platforms, a detailed analysis was presented, considering the kinetic profiles for obtaining cellobiose, glucose, xylose and arabinose. For the conditions evaluated, a different behavior was identified in relation to the process parameters and the best results were 7.11 and 9.28 g/100 g of biomass of fermentable sugars and chemical platforms obtained synergistically, respectively, after 30 min, 20 MPa, 260 °C and 50 g H2O/g biomass. Furthermore, 17.59 g bio-oil/100 g of biomass was obtained at 340 °C at the same solvent/feed ratio. Analysis of the functional groups on the surface of the bio-oil corresponds to the presence of aldehydes, carboxylic acids, ketones, hydrocarbons, ethers, as well as aromatic, alcoholic and nitrogenous compounds. Similar hydrochar yields were achieved between the conditions, with 24.68 g/100 g of biomass being obtained at 340 °C and a ratio of 50 g of H2O/g biomass, with a higher calorific value of 29.14 MJ/kg (1 .5 times greater than natural biomass). Therefore, the results presented provide innovative information regarding the hydrothermal processing of residual lignocellulosic biomass, especially sawdust.